Chapter 20 The smells of eternity Aromatic oils and resins in the Phoenician mortuary record - Dixon, Helen (Taylor & Francis, 2022)
This chapter surveys and analyses the aromatic substances associated with burial and the preservation of the dead in the Iron Age Phoenician Levant (c. 1100-300 BCE), as part of an exploration of the lost smellscapes of the ancient world. First, Phoenician vocabulary related to smelling and pungent substances is outlined and investigated. Then, a review of coastal Levantine archaeological and textual evidence, along with comparanda from the wider Mediterranean world, is used to establish the range of smells and substances that would have been associated with mortuary practice at this time. While oleo-resins in use in the burial record overlap to some degree with those used in everyday life-in perfumes, religious practice, and other uses of scented oils and incense-the unique constellations of aromatics used to inter the dead highlight the importance of these deeply mnemonic sensory elements in our understanding of the Iron Age past.